Supragingival microbiome variations and the influence of Candida albicans in adolescent orthodontic patients with gingivitis - Hao Yang; Yansong Ma; Hongyu Gao; Xianju Xie; Hongmei Wang; Xiaowei Li; Yuxing Bai (Journal of Oral Microbiology)
Introduction Gingivitis is a prevalent complication in adolescents undergoing fixed orthodontic treatments. However, changes in the supragingival microbiome associated with gingivitis and the impact of Candida albicans remain elusive. Therefore, we investigated supragingival microbiome discrepancy and C. albicans colonization in adolescent orthodontic patients with gingivitis.Methods Dental plaques were collected from 30 gingivitis patients and 24 healthy adolescents, all undergoing fixed orthodontic treatment. The supragingival microbiome composition was analyzed using 16S rRNA sequencing. C. albicans colonization was determined using fungal culture and real-time quantitative polymerase chain reaction.Results Our analysis revealed significantly heightened microbial diversity in the Gingivitis group. Notably, patients with gingivitis exhibited an enrichment of periodontal pathogens, such as Saccharibacteria (TM7) [G-1], Selenomonas, Actinomyces dentalis, and Selenomonas sputigena. Additionally, 33% of the gingivitis patients tested positive for C. albicans, exhibiting significantly elevated levels of absolute abundance, while all healthy patients tested negative. Significant differences in microbial composition were also noted between C. albicans-positive and -negative samples in the Gingivitis group.Conclusion Significant disparities were observed in the supragingival microbiome of adolescent orthodontic patients with and without gingivitis. The presence of C. albicans in the supragingival plaque may alter the microbiome composition and potentially contribute to gingivitis pathogenesis.